Eco-social State in the European Union: the Relationship Between the Social and Climate Policy of the Member States - Kaklauskaitė, Ulijona; Navickė, Jekaterina (Socialinė teorija, empirija, politika ir praktika, 2021)
This article analyzes the relationship between the social and climate policies of the European Union member states and examines the concept of the eco–social state. In the climate crisis era, the need for a close link between social and climate policies is particularly acute. The European Green Deal and other EU strategies reflect a political agenda with a specific interest in social and ecological goals. We aim to answer whether more significant state efforts in the social field are related to a similarly more substantial commitment in climate policy or whether a greater focus on one means less attention on another. On a theoretical level, we discuss the challenges of climate change for social policy and present the concept of climate justice. The similarities and differences between the ecological and the welfare state are also examined. We argue that the concept of climate justice highlights the phenomenon of a double and even triple injustice on a global level, which requires joint efforts in spheres of social and climate policy. Eco-social state combines social and environmental institutions intending to ensure welfare and sustainability and thus complements the traditional concept of the welfare state. The Koch-Fritz (2014) classification, which distinguishes between the established, deadlocked, emerging, and failing eco-social states, is presented in the paper and used for the empirical analysis. The empirical part of the paper employs non-parametrical correlation and hierarchical cluster analysis. The former allows for exploring the links between the ecological and social indicators. The latter enables countries to be grouped according to social and climate indicators and compared to the traditional classification of welfare states and Koch-Fritz models of eco-social states. The analysis is based on social and climate indicators of the Europe 2020 strategy. The study found that countries that provide relatively more significant funding for traditional social problems also perform better in climate change adaptation and mitigation policies by reducing greenhouse gas emissions in an effort–sharing sectors and final energy consumption. We show that clusters of the EU member states in terms of social and climate indicators (eco–social state models) are very similar to their membership in the traditional welfare states’ classification.Moreover, social democratic welfare states are better prepared to address climate change than countries representing other types of welfare states. Thus the analysis confirms the social democratic welfare states as established eco–social states, while the conservative-corporate and liberal welfare states can indeed be called deadlocked eco–social states with average results. We show, however, that Lithuania, together with other Eastern European and Southern European countries, fluctuates on both the best and the worst social and climate change mitigation outcomes. Hence those should be attributed to a group with the mixed results and can be named as failed-emerging eco-social states.
Keywords: welfare state; climate policy; European Union; eco-social state